IMPLEMENTATION OF THE POOR RICE PROGRAM IN AN EFFORT TO SUPPORT AND IMPROVE COMMUNITY FOOD SECURITY (CASE STUDY IN AIR MATA VILLAGE, KOTA LAMA DISTRICT, KUPANG CITY) - Adri Ketmoen (Jurnal REP (Riset Ekonomi Pembangunan), 2022)
This study aims to determine the description of the implementation of the distribution and impact of the Raskin program (Indonesian rice distribution program for the poor) for target beneficiary households (RTS-PM). This type of research is descriptive qualitative with survey and documentation methods. The results of the study are known to be the implementation of the Raskin program in Airmata Village, which is measured by 6T success indicators (right target, correct quantity, right time, right quality, right administration, and right price); it can be concluded that the implementation has been running but not yet optimal, caused by indicators of the right amount, right quality, and on time out of sync with conditions in the field. The Raskin program has a positive impact and benefits the recipient community because of the relatively affordable prices and the well-running routine program to support and improve community food security.